?COPPER(I) COMPLEXES OF TRIPHENYLPHOSPHINE AND 2-METHYLPYRIDINE - SULTANA, NAJMA; ARAYNE, M. SAEED; TABASSUM, HAMlDA (Biological Sciences - PJSIR, 1997)
Copper (1)complexes with triphenylphosphine and o-picoline have been prepared. The variation in stoichiom- etry and the probable structures of these complexes have been discussed on the basis of their chemical and spectral data; these complexes have been suggested to have dimeric structure and the experimental data are in support of the bridging of halides, nitrate or thiocyanate groups between the two copper atoms.